Northern Reformations: Introduction - Berg, Sigrun Høgetveit; Kristiansen, Roald E; Dahl Hambro, Cathinka (Nordlit, 2019)
What did the protestant reformations look like in the very north of Europe? How did the cultural, political and economic consequences of the religious change influence the relationship between Scandinavia, the British Isles and continental Europe? Various questions related to these main themes were the topics for discussions at the conference “Northern Reformations” in Tromsø, Norway, September 21–22, 2017. This Nordlit volume contains papers based on most of the conference contributions.